Age-related morphometrical peculiarities of Lithuanian women's primordial ovarian follicles - Kristina Lasiene; Donatas Gasiliunas; Nomeda Juodziukyniene; Aleksandras Vitkus (BMC, 2018)
Abstract Background For the first time, thorough morphometrical measurements of primordial ovarian follicles were performed and their age-related changes were investigated in Lithuanian women of the reproductive age. Methods Ovaries of dead women (n = 30) were divided into six age groups: 15-20 years old, 21-25 years old, 26-30 years old, 31-35 years old, 36-40 years old and 41-46 years old. Histological slides of left and right ovaries were stained using haematoxylin-eosin and periodic acid-Schiff (PAS) staining methods. The morphometrical measurements of 10 primordial ovarian follicles of the left and right ovary of each woman were made from microphotographs. Results The diameter of primordial ovarian follicles increased in groups of women from 15 years old to 35 years old and decreased in the groups from 36 years old to 46 years old. The area of primordial ovarian follicles increased in the groups of women until 35 years old. It decreased in the groups of women older than 36 years. The follicular basement membrane thickened from 1.29 ± 0.11 μm to 1.43 ± 0.18 μm with increasing age of women. The diameter of primary oocytes enlarged until 35 years and then began to decrease. The area of primary oocytes increased in women until 35 years. It decreased in groups of women aged 36-40 and 41-46 years old. The diameter and the area of primary oocytes nuclei increased in women aged 15-30 years old; later, it began to decrease. The length of follicular cells varied from 8.56 ± 0.43 μm to 8.72 ± 0.27 μm (p > 0.05). The height of follicular cells varied from 2.59 ± 0.27 μm to 2.7 ± 0.21 μm (p > 0.05). The diameter, the area and the basement membrane thickness of primordial ovarian follicles and the diameter and the area of primary oocytes and their nuclei differed insignificantly in left and right ovaries in all age groups of women (p > 0.5). The length and height of follicular cells were similar in left and right ovaries of the same age group (p > 0.5). Conclusions The age decreasing of morphometrical parameters begins in primordial ovarian follicles and their primary oocytes in Lithuanian women older than 35 years. The thickness of the follicular basement membrane increased with increasing age of women. No significant differences were found in the morphometrical parameters in primordial follicles of left and right ovaries in the same age group of women.